Determine the suicidal risk, as well as psychological well-being and the family structure of young new entrants to the health careers - Eguiluz R., Luz de Lourdes (2014)
The purpose of this research is to determine the suicidal risk as well as psychological well-being and relate these two variables with the family structure of young new entrants to the Health Careers. This was assessed with three instruments: Family Adaptability and Cohesion Evaluation Scale (FACES IV), the IRIS for suicide risk, and the Subjective and Psychological Well-Being Scale. Results show, respect to the family structure, that 87% of the participants think that their family is chaotic and 28 % consider that their family is not cohesive. Results of the IRIS showed that eight of the 329 were identified with high suicidal risk, eleven with high risk of depression and ten students lack of factors that can protect them from the risks to which they are exposed. Finally, the perception of their well-being in 71 of the 329 young people is very low, so they are found in possibility of depression or even being at risk of suicide.